QNP_SHELL: A computerized tool for improving decision-making skills for nuclear power plant operators - Hassan Qudrat-Ullah (Cogent Engineering, 2015)
Decision-making in complex systems such as nuclear power plants (NPPs) is a difficult task at best. The safety and integrity of many such high-capital cost-intensive installations depend on the operator’s capability to correctly diagnose and take appropriate measures to avoid any abnormal operations of an NPP. Therefore, the role of the expert systems in the offline training programs for the operators is ever increasing. In this paper, we describe the development of an expert system, “QNP_SHELL,” to assist, offline QNPP operators and plant personnel in a better familiarization to infer the anticipated and foreseen malfunctions from the observed symptoms. QNP_SHELL’s inferencing mechanism is of the “Rule-based” type and to search the knowledge base it adopts the “Depth First” technique. The diagnostic performance of the trainee operators using QNP_SHELL on various accidents at QNPP has been found, through both the qualitative and quantitative evaluations, satisfactory.